The effect of strain rate on the determination of mechanical properties of steel bar for reinforced concrete - Lamo, Werachai (Bulletin of Applied Sciences, 2022)
In tensile test, most of testing standards specify applicable strain rates because of that the materials will yield at different strength levels and are slightly sensitive to the strain rates for the tensile strength. The materials tested in according to the testing standards should present equivalent strength values without considering which test laboratory performs the tensile test. The presented material strength may depend upon the used strain rates. Therefore, the question comes up whether or not different strain rates have an effect on the mechanical properties of the tested materials. Referring to the testing standard of steel bar for reinforced concrete, it is required to know definite minimum values of the mechanical properties of steel bar for reinforced concrete, such as yield strength, tensile strength, elongation, reduction of area, and elastic modulus. Therefore, testing laboratories have to test for gaining reliable mechanical property information, which will lead to the exact utilization. This can avoid severe damage, loss of life, and high expense in maintenance. This research study aimed to study the effect of different strain rates (0.000185 s-1, 0.000555 s-1, 0.001296 s-1, 0.002222 s-1, 0.011111 s-1, and 0.02963 s-1) on the mechanical property values (such as yield strength, tensile strength, elongation, and reduction of area) of steel bar for reinforced concrete by considering the strain rate sensitivity ( ). The experimental results showed that different strain rates had an impact on the mechanical property values. When the strain rate was increased, the tensile strength tended to decrease (around 13 MPa) and the yield strength tended to increase (around 19 MPa), according to the strain rate sensitivity for the tensile strength m=-0.0024 and the strain rate sensitivity for the yield strength m=0.0045, respectively. The increasing of the strain rate had more effect on the yield strength than the tensile strength. In addition, the uncertainties of the yield strength (about ±30 MPa และ ±47 MPa, respectively) and tensile strength (about ±60 MPa และ ±82 MPa, respectively) were higher at the minimum strain rate and the maximum strain rate. Moreover, when the strain rate was increased, the elongation tended to decrease (approximately 3%) and the reduction of area tended to slightly increase (approximately 1%), according to the strain rate sensitivity for the elongation m=-0.0341 and the strain rate sensitivity for the reduction of area m=-0.0032, respectively. When the strain rate was increased, the elongation significantly decreased. In contrast, the reduction of area slightly increased or barely changed. In addition, the uncertainties of the elongation (approximately ±0.2%) and reduction of area (approximately ±0.3%) were risen very slightly, when the strain rate was increased.